A proposal to introduce digitalization technologies within the automation learning process. Issue 2 (2020) - Iriondo, N.; Orive, D.; Casquero, O.; Marcos, M.
Abstract: Although the digital factory (DF) concept has raised high expectations since its inception, it is still missing industrial impact. One of the problems attributed to this issue is the lack of education curricula for enhancing the related digital competences of the future professionals. Higher education institutions, as major stakeholders in education, should introduce the new technologies for DF in practical courses. However, it is difficult to deal with the complexity of those technologies in a time-limited environment such us a bachelor or a master course. Instead of providing complete knowledge, this paper proposes to focus on the methodological aspects that allow students to acquire the skills needed to handle those technologies. Specifically, this paper illustrates this approach for teaching virtual commissioning (VC) within the automation learning process. The goal is to show the students how to use powerful industrial tools for performing VC through a set of methodological steps that help students manage the complexity of the VC process regardless of the specific tools used for it.